PENGUATAN BUDIDAYA PADI GENJAH M70D BERBASIS PUPUK ORGANIK DAN IRIGASI SUMUR DALAM : PENDEKATAN PARTISIPATIF IP400 DI DESA BANYU URIP - Lolita Endang Susilowati; Suwardji Suwardji; Wayan Wangiyana; Sukartono Sukartono; Dori Kusuma Jaya; Isnaniar Rahmatul Azizah (Universitas Mataram, 2025)
This community service activity was held on May 25, 2025 in Banyu Urip Village, Gerung District, West Lombok involving 45 farmers. This program aims to increase the capacity and adoption of M70D variety genjah rice cultivation technology to support the IP400 intensification system. The methods used include counseling, field demonstrations, and participatory-based mentoring, accompanied by pre-post test evaluation. The results showed a significant increase in farmers knowledge from 35% to 85% in the aspect of rice cultivation, and from 40% to 80% in weed control. Demonstrations on 6.2 acres of pilot land were actively attended by farmers and resulted in the early adoption of SRI (System of Rice Intensification) practices, and organic fertilization. Periodic assistance strengthens the application of cultivation techniques and the readiness of farmers to implement technology on their respective lands, This program demonstrates the effectiveness of a participatory approach and the use of local resources in increasing the technical capacity and sustainability potential of the IP400 system.